Identification and Comprehensive Analysis of FREM2 Mutation as a Potential Prognostic Biomarker in Colorectal Cancer - Du, Hanpeng; Wang, Haiyue; Kong, Fandong; Wu, Mingjian; Chen, Wei; Lyu, Jin; Zhou, Sitong; Yang, Ronghua (Frontiers in Molecular Biosciences, 2022)
Gene mutations play an important role in tumor progression, and the study aimed to identify genes that were mutated in colorectal cancer (CRC), and to explore the biological functions of gene mutations and the prognostic value for CRC patients. Downloaded data sets from TCGA and ICGC and perform somatic mutation analysis. FREM2 was identified with the highest mutation frequency. COAD patients were divided into FREM2 mutation type (n=36) and FREM2 wild type (n=278), and KM curve was used to perform prognostic analysis. The random forest (RF) method was used to construct a FREM2 mutation prognosis model, and the performance of the model was evaluated by ROC. Next, RF method and Cox regression analysis were used to construct a prognostic model based on the gene expression data of 36 FREM2 mutant RCR patients. The model shown to have a high prediction accuracy (83.9%), and 13 prognostic model characteristic genes related to OS were identified. Then, the results of TMB and MSI analysis found that there were significant differences in TMB and MSI among the risk score samples of different prognostic models. Differentially expressed genes were identified and analyzed for functional enrichment and immune infiltration. Finally, 30 samples of CRC patients were collected for immunohistochemical staining to analyze the expression level of FREM2, and it was found that FREM2 was highly expressed in tumor tissues. In conclusion, CRC patients had a high level of FREM2 mutations associated with a worse prognosis, which indicated that FREM2 mutations may be potential prognostic markers in CRC.